Effects of hydration on the mechanical properties of deep shale under true triaxial stress: A case study of Fuling shale gas in Sichuan Basin, SW China - Jinzhou ZHAO; Zhihao YU; Lan REN; Ran LIN; Jianfa WU; Yi SONG; Cheng SHEN; Ying SUN (Petroleum Exploration and Development, 2025)
This study takes shale samples from the Jiaoshiba block in the Fuling shale gas field of the Sichuan Basin, and uses the true triaxial testing system to conduct a series of mechanical experiments under deep shale reservoir conditions after shale hydration. Stress-strain data and mechanical parameters of shale after hydration under high temperature and high pressure were obtained to investigate the effects of reservoir temperature, hydration time and horizontal stress difference on the mechanical strength of shale after hydration. By using nonlinear regression and interpolation methods, a prediction model for the mechanical strength of shale after hydration was constructed, and the mechanical strength chart of deep shale under high stress difference was plotted. First, higher hydration temperature, longer hydration reaction time, and greater horizontal stress difference cause shale to enter the yield stage earlier during the compression process after hydration and to exhibit more prominent plastic characteristics, lower peak strength, peak strain, residual strength and elastic modulus, and higher Poisson’s ratio. Second, the longer the hydration time, the smaller the impact of hydration temperature on the mechanical strength of deep shale. As the horizontal stress difference increases, the peak strength and residual strength weaken intensely, and the peak strain, elastic modulus and Poisson’s ratio deteriorate slowly. Third, the mechanical strength of shale decreases significantly in the first 5 days of hydration, but gradually stabilizes as the hydration time increases. Fourth, the visual mechanical strength chart helps to understand the post-fracturing dynamics in deep shale gas reservoir fracturing site and adjust the drainage and production plan in time.